PRÉDICTION DE LA DÉFAILLANCE DE LA CLIENTÈLE DU MICRO CRÉDIT AU MAROC : LA MÉTHODE DES SCORES - Omar Taouab (European Scientific Journal, ESJ, 2014)
Growth of microfinance in Morocco dates from the mid 1990s and became particularly active during the 2000s. Currently , the sector began to experience multiple risks including the credit .Indeed, credit risk , which may hinder the emergence of micro-finance institutions , has become one of the main concerns of financial institutions. Thus, an important place should be reserved for the art of risk management of the borrowers notably through the anticipation of their failure. This goal is achievable in advance through the use of a technique scores which allows you to assign an individual to one of the groups namely the right customers and failed. Drawing lessons on discrimination function presented by ( Saporta , 1975) , the judgment can be made according to the socio -economic and demographic characteristics of each customer and given the form taken by the different variables. The calculation of scores allowed us to develop a discrimination filter for note customers , identify classes of risk and identify those likely to get faulty at the time of repayment.